Enhancing healthcare utilization and reducing preventable hospitalizations: exploring the healthcare-seeking propensity of patients with non-communicable diseases in Rural China - Yanqiu Hou; Wenyu Li; Shangai Li; Linxuan Chen; Jiayu An; Shan Lu (BMC Public Health)
Abstract Objective Understanding healthcare-seeking propensity is crucial for optimizing healthcare utilization, especially for patients with chronic conditions like hypertension or diabetes, given their substantial burden on healthcare systems globally. This study aims to evaluate hypertensive or diabetic patients’ healthcare-seeking propensity based on the severity of symptoms, categorizing symptoms as either major or minor. It also explores factors influencing healthcare-seeking propensity and examines whether healthcare-seeking propensity affects healthcare utilization and preventable hospitalizations. Methods A cross-sectional study was conducted in 2023 in rural areas of Dangyang city, Hubei province, and Xishui county, Guizhou province. A sample of 780 patients, including those with hypertension, diabetes, or both, was obtained using multistage stratified cluster sampling. Healthcare-seeking propensity was evaluated using a questionnaire with two subscales for major and minor symptoms, which were analyzed separately. Multiple linear regression was used to identify factors influencing healthcare-seeking propensity, while logistic regression was employed to examine the relationship between healthcare-seeking propensity and healthcare utilization, as well as preventable hospitalizations. Results Rural Chinese patients had an average healthcare-seeking propensity score of 5.43 ± 1.99 for major symptoms and 8.04 ± 1.66 for minor symptoms. Factors such as age, education level, income, accessibility to healthcare, and enrollment in family doctor services influenced healthcare-seeking propensity for both types of symptoms. Patients’ self-rated health status and the type of disease affected their healthcare-seeking propensity for major symptoms, while primary healthcare service quality solely impacted the propensity for seeking care for minor symptoms. Logistic regression demonstrated that after accounting for confounding factors, a higher propensity for seeking care for minor symptoms was associated with increased healthcare service utilization (AOR = 1.402, 95% CI: 1.259–1.562), whereas a higher propensity for major symptoms remarkably reduced preventable hospitalizations (AOR = 0.501, 95% CI: 0.428–0.587). Conclusions Rural Chinese patients exhibited different healthcare-seeking propensity depending on the type of symptoms. The healthcare-seeking propensity in the western region was lower than that in the central region, highlighting regional disparities. Seeking care for minor symptoms results in more outpatient visits, whereas addressing major symptoms reduces preventable hospitalizations. Establishing a robust network of primary healthcare facilities and emphasizing the role of family doctors can boost patients’ propensity to seek healthcare. Clinical trial number Not applicable.